2018
DOI: 10.1111/cns.13075
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor gene variants are associated with emotion recognition and resilience, but not with false‐belief reasoning performance in healthy young Korean volunteers

Abstract: Summary Aims A growing body of literature has indicated that oxytocin is associated with several domains of social cognition and behavior. Nevertheless, the effects of oxytocin receptor gene (OXTR) polymorphisms on social phenotypes remain unclear. Therefore, we aimed to explore the genetic influence of OXTR variants on social cognition (social perception and theory of mind) and resilience in healthy individuals. Methods We examined the influence of 10 common OXTR variants on social cognitive abilities, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Therefore, it is reasonable that the two SNPs have similar regulating effects on sleep quality. Moreover, the other three SNPs in this study were associated with empathy in recent studies (Christ et al, 2016; Kim et al, 2019; Wu et al, 2012). Considering that ASD (Missig et al, 2020) and different aspects of empathy (Deliens et al, 2018; Guadagni et al, 2018) were correlated to sleep issues, it is possible to discover genotype–genotype interactions of the OXTR gene polymorphisms on self‐reported sleep quality.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, it is reasonable that the two SNPs have similar regulating effects on sleep quality. Moreover, the other three SNPs in this study were associated with empathy in recent studies (Christ et al, 2016; Kim et al, 2019; Wu et al, 2012). Considering that ASD (Missig et al, 2020) and different aspects of empathy (Deliens et al, 2018; Guadagni et al, 2018) were correlated to sleep issues, it is possible to discover genotype–genotype interactions of the OXTR gene polymorphisms on self‐reported sleep quality.…”
Section: Discussionsupporting
confidence: 62%
“…Prior evidence suggested that some candidate single‐nucleotide polymorphisms (SNPs) of the OXTR gene were associated with social and emotional functions. For example, rs2254298, rs2268498, rs13316193, rs2268490 and rs2268491 were involved in promoting sociobehavioural domains (Christ et al, 2016; Kim et al, 2019; Wu et al, 2012). Rs2268498 was also associated with stress reactivity (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, A-ASD-carriers presented more social deficits 26 and lower serum OXT-levels 52 . This allele has also been related to prosopagnosia 53 , high levels of physical aggression and hostility 54 and low emotion recognition and resilience skills 55 . G-carriers showed higher levels of retrospective self-report of inhibition and adult separation anxiety 56 and, compared to A-carriers, are more vulnerable to antisocial behavior if they experience maltreatment 57 .…”
Section: Resultsmentioning
confidence: 99%
“…One study investigated the OXTR variant rs2254298 on psychological resilience as measured by CD-RISC ( 106 ). The authors found a dose-dependent effect of the A allele in ethnically Korean adolescents and young adults, with highest resilience in carriers of the GG genotype, decreasing by 3.84 on the CD-RISC scale with a one-copy increase in the A allele.…”
Section: Resultsmentioning
confidence: 99%